Metode Latihan Interval (Interval Training) sebagai Upaya Meningkatkan Volume Oxigen Maximum (VO2Max) Pemain Futsal Wanita - Chaeroni, Ahmad; Rido, Muhamad; Bahtra, Ridho; Gemaini, Andri (Jurnal Sporta Saintika, 2023)
The interval training method is one form of exercise that is expected to increase Volume Oxigen Maximum (VO2Max), especially for female futsal players. The purpose of this study was to determine how much influence the interval training method has on increasing VO2Max for female futsal players. Method The approach in this study used the "Pretest Posttest Design involving 12 female futsal players of Rimbo girl Tebo Regency. Participants were obtained based on certain criteria that were met. The instrument used in obtaining VO2Max data uses the yo-yo test. The data were analyzed using the "t-test" test analysis with a significant level of 0.5 using spss. The results showed an increase in VO2Max of female futsal players when viewed from the results of pretest and posttest data. So that there is an effect of the interval training method on VO2Max futsal players. This is proven significantly, where after the "t" test is carried out the results of tcount = 16.43> ttable = 1.796. Thus it can be concluded that there is an effect of interval training on increasing VO2Max of futsal players Gadis Rimbo Tebo district